Developing a prototype underwater remotely operated vehicle (ROV) for MFI's technical education and training modules - Angeles, Ernesto M. Jr (Technology Management Center, 2009)
MFI and Subnet Services Ltd has signed a Memorandum of Understanding in sub-contracting MFI to deliver technical training required by ROV Pilot Technician training. This is designed primarily for Subnet's ROV 3-in-1 Electronics with Fiber Optics, Hydraulics and High Voltage Electrical. This project is designed particularly for Electronics with Fiber Optics of which divided into two (2) parts : the Practical Electronics which includes Basic and Analog Electronics; and Advanced Electronics which includes Digital Electronics, DAC, ADC, Fiber Optics and ROV Project making. This project is part of an ongoing effort to incorporate innovative, hands on projects into the ROV 3-in-1, specifically, Electronics. This prototype Underwater ROV project when finished and tested, will be replicated as training modules that would help expose foreign delegates as well as MFI students to practical design issues in the course, foster creative problem solving skills and may aid foreign delegates and MFI students retention of learning and application in real world of ROV Pilot Technician-Electronics. We describe ongoing work to extend this project to include microcontroller and sensory feedback, allowing delegates and students to experience "almost" real underwater ROV. The main project objective of the team is the design and manufacture of a prototype remotely operated underwater vehicle. This vehicle to be controlled remotely by an offshore pilot using solely the aid of onboard watertight cameras for guidance. The vehicle is tethered (connected) to the shore by a multiple wire electrical cable carrying power, control and video signals. The vehicle gets its maneuverability from 5 mounted electrical thrusters. The ROV must be able to dive, float, forward and reverse maneuver. The lateral movement/maneuver will be integrated later of the design/development. The device has positive buoyancy, so the task will be complete when enough weights have been removed/added for the device to float to the surface. The vehicle must also have the ability to collect up to 3 of these weights and bring them to surface for retrieval, if grabber or the manipulator is attached.